EVOLUSI PEMIKIRAN EKONOMI ISLAM KAJIAN KOMPARATIF AYAT MAKKIYAH DAN MADANIYAH - Ramdhani ilham, Rizky Amaliyah; Nasrullah Bin Sapa (Adpertens: Jurnal Ekonomi dan Manajemen, 2025)
In the study of the Qur'an, the terms Makkiyah and Madaniyah are used to classify verses based on the time and place of their descent. The difference in the characteristics of these verses reflects the social, economic, and political conditions of the time, which also influenced the evolution of Islamic economic thought. This study uses a descriptive method based on literature study to explore the relationship between Makkiyah and Madaniyah verses and Islamic economic principles. The results of the study show that the Makkiyah verse emphasizes the principles of monotheism, justice, and economic morality, while the Madaniyah verse focuses more on the regulation of the practical economic system, such as zakat, inheritance, and muamalah. Islamic economic thought continues to develop from basic principles in the era of the Prophet Muhammad PBUH to contemporary theories that integrate sharia with modern practices, such as Islamic banking. This study emphasizes the importance of understanding the verses of Makkiyah and Madaniyah in forming a just and sustainable Islamic economic system.